2021
DOI: 10.1177/19476035211011520
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid–Binding Protein 4 (FABP4) Is Associated with Cartilage Thickness in End-Stage Knee Osteoarthritis

Abstract: Background There is no single blood biomarker for the staging of knee osteoarthritis (KOA). The purpose of this study was to assess the relationship of obesity, serum biomarkers, the hip-knee-ankle angle (HKAA) with sonographic cartilage thickness. Methods We conducted a cross-sectional study of n = 33 patients undergoing knee arthroplasty. Body mass index (BMI) was recorded, and patients were grouped based on BMI. Serum blood samples were collected, and the following biomarkers were measured using the ELISA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 46 publications
1
11
1
Order By: Relevance
“…Previous studies have reported that downregulation of FABP4 promotes osteoclast formation (9). However, contrary to our findings, it has been reported that FABP4 is up-regulated in SF and plasma in individuals with OA (10, 11). Follistatin-like protein 3 (FSTL3) is a glycoprotein that is involved in regulating inflammation and suppresses osteoblast differentiation of bone marrow mesenchymal cells during that process(12).…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have reported that downregulation of FABP4 promotes osteoclast formation (9). However, contrary to our findings, it has been reported that FABP4 is up-regulated in SF and plasma in individuals with OA (10, 11). Follistatin-like protein 3 (FSTL3) is a glycoprotein that is involved in regulating inflammation and suppresses osteoblast differentiation of bone marrow mesenchymal cells during that process(12).…”
Section: Discussioncontrasting
confidence: 99%
“…Our pilot data also demonstrated that FABP4 has effects on chondrocytes in a dose‐dependent manner 3 . Similar results were observed in other studies investigating the role of FABP4 in OA 13,14 . The role of FABP4 in rheumatoid arthritis has also been recently reported 28 .…”
Section: Discussionsupporting
confidence: 90%
“…FABP4 is expressed in vascular endothelial cells of meningiomas, especially anaplastic meningiomas, and may serve as a potential marker (Lee et al, 2021b). A small sample size study found a negative correlation between FABP4 and cartilage thickness in end-stage knee osteoarthritis (Schadler et al, 2021). Other studies have shown that FABP4 is associated with kidney stone formation, and downregulation of FABP4 drives calcification, suggesting a link between kidney stones and metabolic syndrome (Taguchi et al, 2020).…”
Section: Othersmentioning
confidence: 98%